Operando synchrotron X-ray studies of MnVOH@SWCNT nanocomposites as cathodes for high-performance aqueous zinc-ion batteries. Issue 27 (29th June 2022) - Gull, Sanna; Huang, Shao-Chu; Ni, Chung-Sheng; Liu, Shih-Fu; Lin, Wei-Hsiang; Chen, Han-Yi
Abstract : MnVOH@SWCNTs shows a high capacity up to 381 mA h g −1 over 300 cycles. Operando XANES confirms the change in oxidation states and operando XRD shows the reversible change in the crystal structure during the cycling process. Abstract : Aqueous zinc-ion batteries (AZIBs) have great potential as energy-storage devices because of their low cost and environmental friendliness. However, the key challenge for rapid and reversible Zn 2+ for AZIBs is the generation of a stable and efficient cathode material. Herein, we prepared a scalable synthesis method, based on a low-temperature (120 °C) hydrothermal route, to prepare Mn0.19 V2 O5 ·2.34H2 O (MnVOH), which was incorporated into a single-walled carbon nanotube (SWCNT) network, and subsequently utilized as the AZIB cathode material. Furthermore, the MnVOH@SWCNT nanocomposite material ensured close interaction between MnVOH and SWCNTs, with a continuous network structure, and expanded interlayer spacing that provided fast electron transfer kinetics ( D Zn 2+ : 10 −11 to 10 −12 cm 2 s −1 ). This resulted in an excellent rate performance of 81% during cycling. Consequently, the resultant batteries possessed a significantly enhanced intercalation storage capacity of 381 mA h g −1, at a current density of 0.1 A g −1, and reduced polarization with a high capacity retention of 89% over 300 cycles (at 5 A g −1 ). Furthermore, operando synchrotron X-ray absorption near-edge spectroscopy (XANES) was studied for the first time to verify the Zn 2+ charge-storage mechanism. To further understand the structural changes of the MnVOH@SWCNT nanocomposite during the discharge/charge process, operando synchrotron X-ray diffraction (XRD) measurements were also performed. In addition, the MnVOH@SWCNT nanocomposite material could sustain a high energy density of ca. 194 W h kg −1 at a high-power density of 3.2 kW kg −1, which is higher than that of MnVOH, thus demonstrating that MnVOH@SWCNTs is a promising candidate as a high-performance cathode material for AZIB applications.